The origin of the modern Jewish woman writer : romance and reform in Victorian England - Galchinsky, Michael (Wayne State University Press, 1996)
Between 1830 and 1880, the Jewish community flourished in England. During this time, known as haskalah, or the Anglo-Jewish Enlightenment, Jewish women in England became the first Jewish women anywhere to publish novels, histories, periodicals, theological tracts, and conduct manuals. The Origin of the Modern Jewish Woman Writer analyzes this critical but forgotten period in the development of Jewish women's writing in relation to Victorian literary history, women's cultural history, and Jewish cultural history. Michael Galchinsky demonstrates that these women writers were the most widely recognized spokespersons for the haskalah. Their romances, some of which sold as well as novels by Dickens, argued for Jew's emancipation in the Victorian world and women's emancipation in the Jewish world.